Capturing problematic urban Canada geese in Reno, Nevada: Goose roundups vs. use of alpha-chloralose - Smith, Mike A. (eScholarship, University of California, 2004)
Urban Canada geese, in large numbers, have exploited human manipulation of the Reno, Nevada cityscape, creating human health and safety concerns along with monetary losses to businesses and private citizens. A primary concern from the start has been the potential for an aircraft-bird strike at the Reno-Tahoe International Airport. To address this urban goose problem, USDA APHIS Wildlife Services (WS) “rounds up” the problem geese by use of a funnel trap, where a gathering cage is placed at the junction of two plastic fence wings. Goose roundups occur on golf courses, city parks, and private residences. The use of the traps can be labor intensive on some properties, often requiring the coordination of federal, state, and city employees in addition to volunteers, to assure adequate personnel are available. A goose roundup is generally a high-profile public affair. WS makes every effort to start roundups early in the morning (4:00-4:30 A.M.) to avoid crowds, and more importantly, to reduce heat stress to the geese. However, there always seem to be a few citizens observing the operation. For many people, the sight of 20 to 30 geese enclosed in a small cage, honking and hissing, and potentially trampling goslings under foot, can be quite upsetting. Many urbanites only encounter Canada geese at the city park, where they typically enjoy feeding the local population. This limited exposure often results in negative reactions to goose capture and relocation efforts. To reduce the need for high-profile roundups in urban areas, WS experimented with the use of alpha-chloralose (AC) on urban geese located in select parks and gated communities. Alpha-chloralose is an avian tranquilizer that is administered orally to waterfowl through corn or bread bait. We hoped that the use of AC would change public opinion about the stress the geese might suffer during capture efforts. Further, we sought to capture repeat offending geese that had become wise to the funnel trap and avoided capture by that method. Since many properties are not suitable for funnel trap use, we wished to expand the WS urban goose management effort by employing this additional capture method. AC delivery by bread baits allowed for the precise targeting of problem geese. The advantages and disadvantages of both roundups and AC treatments are discussed.